Satisfaction and results of the subareolar incision as treatment for gynecomastia in adolescents: experience of two centers - Andrea Zangari; Carmine Noviello; Camilla Todesco; Mercedes Romano; Letizia Trotta; Carmine Botta; Ilaria Cascone; Salvatore Scommegna; Gabriele Vasta; Vito Briganti; Alfonso Papparella (PAGEPress Publications, 2024)
Gynecomastia is a benign glandular proliferation that can affect adolescents causing significant psychological discomfort. Generally, it is idiopathic but underlying endocrinological conditions must be excluded. Different surgical techniques are available, the surgical correction with subareolar incision achieves the goal of satisfactory aesthetic result for patients. We studied all patients treated for gynecomastia in two centers of pediatric surgery. After collection of a detailed family history, we evaluated the presence of early onset of puberty, congenital abnormalities of the external genitalia, use of drugs, eating habits and the presence of genetic disorders. Laboratory tests and ultrasound were made to exclude endocrinological disorders. The surgical treatment was performed by a subareolar incision with gland and adipose tissue excision. A Body - Q chest module to evaluate patient satisfaction has been proposed to everyone before and after surgery. 47 adolescents with median age of 15 years were surgically treated. Three presented endocrinological disorders. Grade of gynecomastia for surgery was: III in 40 patients and IIb in 7 patients. Postoperative complications occurred in 5 patients. The Body - Q chest module was completed by 42 patients and showed good results for all points analyzed, except for social feelings. Gynecomastia in adolescents can be surgically treated with subareolar incision, reporting good aesthetic results and low incidence of complications. Specific tests are useful to assess patient satisfaction.